(untitled) - Kruglinski, David J. (Redmond, 1997)
C++ programming for the Internet -- Windows "RM" Sockets, MFC WinInet, and ISAPI extension programs for Microsoft Internet Information Server An enclosed CD-ROM contains valuable sample source code and sample applications developed for the book?all of which makes this volume an indispensable tool that every professional will keep close at hand.
Keywords: C++ (Computer program language),C++ (Ngôn ngữ chương trình máy tính)